STRATEGI OPTIMALISASI MANAJEMEN SARANA PRASARANA DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI MIN I PURBALINGGA - Lany Farikha; Musdalipah Putri; Nursaida; Zainal Arifin Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the strategy for optimizing infrastructure at MIN 1 Purbalingga which in general has been well managed, although it still faces challenges and shortcomings such as playgrounds and places of worship due to limited land and budget. Strategic efforts to overcome this can be implemented through several stages of management including planning, procurement, use, maintenance, supervision, inventory, and disposal, and implemented collaboratively. This study uses a descriptive qualitative approach through observation, interviews, and documentation with the main informant, the head of the madrasah and supporting informants from teachers, students, and parents. The results show that this strategy has a positive impact on the quality of education and strengthens the image of the madrasah. As well as providing recommendations for the management of infrastructure in other elementary education institutions.